1995
DOI: 10.1074/jbc.270.45.26918
|View full text |Cite
|
Sign up to set email alerts
|

Different Antifolate-resistant L1210 Cell Variants with either Increased or Decreased Folylpolyglutamate Synthetase Gene Expression at the Level of mRNA Transcription

Abstract: Growth of one of these variants (L1210/R69), with metoprine in the presence of decreasing concentrations of l,L5-CHO-folateH 4 (natural diastereoisomer of 5-formyltetrahydrofolate), resulted in the selection of other variants (L1210/R82, R83, and R84) with further reduction in one-carbon, reduced folate transport and in two cases (L1210/R83 and R84) with 3-8-fold increased folylpolyglutamate synthetase (FPGS) activity and folate compound polyglutamate formation in situ. Metoprine resistance was further increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Only Galpin et al 56 observed such a relationship in 11 samples obtained from six patients before and after MTX treatment, which may be due to potential upregulation by MTX of FPGS within leukemic blasts. 40 Also in subtypes of cell lines with induced resistance, a relation was found, 35,57,58 but not in a panel of human CEM leukemia cell lines. 59,60 Post-translational modifications may explain this discrepancy since mRNA levels correlated with protein expression, but not with activity of FPGS.…”
Section: Discussionmentioning
confidence: 96%
“…Only Galpin et al 56 observed such a relationship in 11 samples obtained from six patients before and after MTX treatment, which may be due to potential upregulation by MTX of FPGS within leukemic blasts. 40 Also in subtypes of cell lines with induced resistance, a relation was found, 35,57,58 but not in a panel of human CEM leukemia cell lines. 59,60 Post-translational modifications may explain this discrepancy since mRNA levels correlated with protein expression, but not with activity of FPGS.…”
Section: Discussionmentioning
confidence: 96%
“…The human FPGS peptide utilized was deduced from the cDNA nucleotide sequence (23) and linked to keyhole limpet hemocyanin (35). The amino acid sequence of this peptide and its use as an antigen for antibody production has already been described (19). During blotting, the anti-rabbit horseradish peroxidase-IgG conjugate (Sigma) at a 1:3000 dilution was used as the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Derivation of a Murine FPGS cDNA Probe-A murine FPGS cDNA (ZAP-L1210/R83-1) 77.3% homologous to a human FPGS cDNA was obtained by hybridization screening (19) of an L1210 cell cDNA library in gt11 (Stratagene, La Jolla, CA) using the human cDNA, pTZ18U (25), as a probe. This gt11 cDNA construct incorporates a 2.247-kilobase pair insert ligated at the XhoI polylinker site including 3Ј-and 5Ј-untranslated region sequences of 460 and 26 base pairs respectively, and an open reading frame of 1761 base pairs that codes for a putative mitochondrial leader peptide as well as the enzyme protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FPGS enzyme activity was not detectable in human pe-ripheral blood lymphocytes (6), but both enzyme activity and FPGS mRNA increased when the cells were stimulated to proliferate with phytohaemagglutinin (17). Conversely, in a cell line selected for resistance to the second generation dihydrofolate reductase inhibitor edatrexate, the decreased FPGS levels causative of resistance were demonstrated to be due to a decrease in the rate of transcription of the FPGS gene (18). Hence, the limited information available implicates the level of transcription of this gene as the major determinant of cellular FPGS activity.…”
mentioning
confidence: 99%